2008
DOI: 10.4269/ajtmh.2008.79.401
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Water: A Possible Source of Blastocystis spp. Subtype 1 Infection in Schoolchildren of a Rural Community in Central Thailand

Abstract: In January 2005, a survey of intestinal parasitic infections was performed in a primary school, central Thailand. Of 675 stool samples, Blastocystis was identified with a prevalence of 18.9%. Genetic characterization of Blastocystis showed subtype 1 (77.9%) and subtype 2 (22.1%). Study of the water supply in this school was performed to find the possible sources of Blastocystis. Blastocystis from one water sample was identified as subtype 1, which had a nucleotide sequence of small subunit (SSU) ribosomal RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
121
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 38 publications
13
121
2
2
Order By: Relevance
“…close contact with animals that are host to subtypes that can also colonise humans (Alfellani et al, 2013a;Parkar et al, 2010;Wang et al, 2014). Secondly, environmental sources such as drinking water may also be a potential source of Blastocystis (Leelayoova et al, 2008;Taamasri et al, 2000). Poor sanitation and unsuitable water treatment resulting in the consumption of contaminated water are likely to be contributory in this regard (Taamasri et al, 2000;Tan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…close contact with animals that are host to subtypes that can also colonise humans (Alfellani et al, 2013a;Parkar et al, 2010;Wang et al, 2014). Secondly, environmental sources such as drinking water may also be a potential source of Blastocystis (Leelayoova et al, 2008;Taamasri et al, 2000). Poor sanitation and unsuitable water treatment resulting in the consumption of contaminated water are likely to be contributory in this regard (Taamasri et al, 2000;Tan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The reported prevalences of Blastocystis infections in Thailand were approximately 9.9-18.9%. 4,5 To date, several studies reported Blastocystis sp. as a potential pathogenic protozoan.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, the pathogenicity of the infection is still controversial. Since, Blastocystis infection is associated with waterborne transmission 5,8 and is usually found in rural areas in the developing countries, 9 the infection may be a reflection of the poor sanitation of the communities. The study of epidemiology of Blastocystis infection will be helpful to further develop prevention and control efforts to reduce its morbidity among children.…”
Section: Introductionmentioning
confidence: 99%
“…Drinking contaminated water, especially surface water, was reported to be a significant risk factor for Blastocystis infection [22], although in a study made by Abdusalam et al (2013) found no significant difference in the prevalence of Blastocystis infection between those who use treated water and those who use untreated water, indicating that the level of Blastocystis contamination in groundwater is low [4].…”
Section: Discussionmentioning
confidence: 92%
“…In our study only one stool sample remitted to our Laboratory was examined in the majority of individuals, as part of a national surveillance of Parasitic Infections. Previous reports from different countries have shown that Blastocystis infections are associated with several factors such as the consumption of contaminated food and water, close contact with animals, poor personal hygiene, inadequate sanitation, geographical distribution, agricultural activities and seasonal influences [22][23][24]. All samples in this study were remitted from La Habana, and the differences found in the prevalence rates between those studies, representing several provinces, could be related to different water sanitation and geographical distribution.…”
Section: Discussionmentioning
confidence: 99%